2021
DOI: 10.1182/blood-2021-145927
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Related Mutational Signatures Reveal the Origins of Therapy-Related Myeloid Neoplasms

Abstract: Background: Patients treated with cytotoxic chemotherapies and/or autologous stem-cell transplantation (ASCT) are at risk for therapy-related myeloid neoplasms (tMN). As these agents yield increased mutation burden in relapsed malignancies and leave evidence of exposure via mutational signatures, we studied the genomic and temporal relationship between chemo exposure and progression of clonal hematopoiesis (CH) to tMN. Methods: We analyzed 32 tMN whole genomes (WG) from 31 patients [27 acute mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Deeplevel disease quantification allows patients with high levels of cPC within graft or marrow to be offered additional cycles of induction treatment, thereby not only reducing graft contamination but also their overall tumor burden prior to AHCT. In addition, Diamond et al (43) have recently reported clonal hematopoiesis present at myeloma diagnosis to contaminate stem cell graft and after bypass of high-dose melphalan to evolve into secondary malignancies under immunocompromised conditions. This report provides additional evidence toward the emerging importance of graft immune genotyping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deeplevel disease quantification allows patients with high levels of cPC within graft or marrow to be offered additional cycles of induction treatment, thereby not only reducing graft contamination but also their overall tumor burden prior to AHCT. In addition, Diamond et al (43) have recently reported clonal hematopoiesis present at myeloma diagnosis to contaminate stem cell graft and after bypass of high-dose melphalan to evolve into secondary malignancies under immunocompromised conditions. This report provides additional evidence toward the emerging importance of graft immune genotyping.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Diamond et al. ( 43 ) have recently reported clonal hematopoiesis present at myeloma diagnosis to contaminate stem cell graft and after bypass of high-dose melphalan to evolve into secondary malignancies under immunocompromised conditions. This report provides additional evidence toward the emerging importance of graft immune genotyping.…”
Section: Discussionmentioning
confidence: 99%